Fig. 1 in Tissue-specific localization of polyketide synthase and other associated genes in the lichen, Cladonia rangiferina, using laser microdissection - Elshobary, Mostafa E.; Becker, Michael G.; Kalichuk, Jenna L.; Chan, Ainsley C.; Belmonte, Mark F.; Piercey-Normore, Michele D. (Zenodo, 2018)
Fig. 1. Cross sections of thallus tissue of Cladonia rangiferina showing A) the basal older portion with both inner and outer layers, B) the apical younger portion with both inner and outer layers, C) apothecium at the tip of the thallus, D) the basal portion with the inner layer removed by LMD, E) the apical portion with the inner layer removed by LMD, and F) the apothecial tissues removed leaving only the thallus stalk. Each tissue type was removed by LMD to be used in RNA extraction. Published as part of Elshobary, Mostafa E., Becker, Michael G., Kalichuk, Jenna L., Chan, Ainsley C., Belmonte, Mark F. & Piercey-Normore, Michele D., 2018, Tissue-specific localization of polyketide synthase and other associated genes in the lichen, Cladonia rangiferina, using laser microdissection, pp. 142-150 in Phytochemistry 156 on page 144, DOI:10.1016/j.phytochem.2018.09.011, http://zenodo.org/record/10484507